The Use of Osteogenon as an Adjunctive Treatment in Lower Leg Fractures - Piotr Morasiewicz; Monika Zaborska; Michał Sobczak; Łukasz Tomczyk; Paweł Leyko; Andrzej Bobiński; Joanna Kochańska-Bieri; Daniele Pili; Krystian Kazubski (Pharmaceuticals)
Background: The goal of the orthopedic treatment of fractures is to achieve bone union as rapidly as possible in the largest possible number of patients and to minimize the number of complications. The purpose of this study was to assess if the use of Osteogenon would have a positive effect on radiological and clinical parameters in patients with lower leg bone fractures treated with the Ilizarov method. Methods: We evaluated 26 patients who had their lower leg bone fractures treated with the Ilizarov method and received Osteogenon at our clinic in the years 2021–2023. The control group comprised 25 patients with lower leg bone fractures treated with the Ilizarov method who did not receive Osteogenon. We assessed the following parameters: time to achieving bone union, bone union rate, time to resuming normal physical activity, time to achieving pain relief, the number of patients reporting pain relief, and the rate of complications. Results: The median time to achieve bone union after lower leg bone fracture treated with the Ilizarov method was shorter in the Osteogenon group (108.5 days) compared to the control group (134 days), p < 0.001. Bone union was achieved in all the patients in the Osteogenon group and in 96% of the patients in the control group; the difference was not statistically significant. The median time to resuming normal physical activity was shorter in the Osteogenon group (22.5 weeks) compared to the control group (27 weeks), p < 0.001. The median time to achieving pain relief was shorter in the Osteogenon group (21 weeks) compared to the control group (30 weeks), p < 0.001. The proportion of patients who reported pain relief was 88.46% in the group receiving Osteogenon and 76% in the control group; this difference was not statistically significant. The number of complications was lower in the Osteogenon group (8 patients; 30.77%) compared to the control group (15 patients; 60%), p = 0.035. Conclusions: The use of Osteogenon has a beneficial impact on the treatment of lower leg bone fractures with the Ilizarov method. Osteogenon shortens the time to achieve bone union. Moreover, the use of the ossein–hydroxyapatite complex helps reduce the number of complications and shortens the time to achieve pain relief and to resume normal activities.